asynchronous parallel process, Modelling Asynchronous Parallel Process with Petri Net: The asynchronous parallel processes and their structure, the features of the asynchronous parallel process and how to express them in bigram form is the main analysis of this article. Besically, it describes the characteristics and specifications of asynchronous parallel processes and processes in bigram form. The Petri nets are illustrated, the mathematical modeling of asynchronous processes using the Petri net, the marking diagram, the problem of the result and its solutions. Some of the oil and fat production processes were developed and piloted using the Petri net. - Eshankulov, Xamza (Центр Научных Публикаций (buxdu.uz), 2021)
Асинхронные параллельные процессы и их структура, особенности асинхронного параллельного процесса и как выразить их в виде биграмм - главный анализ этого статья. По сути, в нем описаны характеристики и технические характеристики. асинхронных параллельных процессов и процессов в виде биграмм. Иллюстрируются сети Петри, математическое моделирование асинхронные процессы, использующие сеть Петри, диаграмму разметки, проблема результата и ее решения. Немного масла и жира производственные процессы были разработаны и апробированы с использованием Петри сеть.